Were they pushed or did they jump? individual decision mechanisms in education - Gambetta, Diego 1952- (Studies in rationality and social change, 1987)
This book explores the factors which govern the range of educational decisions confronting individuals between compulsory school education and university. The data on which it draws come from two surveys conducted in north-west Italy, one of unemployed young people and one of high-school pupils. The author is in effect testing the two fundamental and opposed paradigms of explanation which are generally applied in the sociology of education; one which holds that the individual agents are essentially passive, being either constrained by lack of alternatives or pushed by causal factors of which they are unaware; and the other in which they are regarded as capable of purposive action, of weighing the available alternatives with respect to some future rewards